CONGENITAL ANOMALIES OF THE VAGINA - Soihet, Samoel (2015)
After a review of the literature on congenital anomalies of the vagina compared with our cases a percentage similarity was found. Agenesis, hypoplasia, transverse and longitudinal septa, hymen, imperforate, mesonefróticos resagos described and consider the cases of adenosis as iatrogenic anomaly. The symptoms of our cases are mentioned and described therapeutic methods do, with an analytical review of our results.